Saving Private Pareto - Harold Houba; Roland Iwan Luttens; Hans-Peter Weikard (Tinbergen Institute, 2013)
We include initial holdings in the jungle economy of Piccione and Rubinstein (Economic Journal, 2007) and relax the assumptions on consumption sets and preferences. We show that initial holdings are irrelevant for lexicographic welfare maximization. Equilibria other than such maximizers can be jungle equilibria due to myopia. We show that farsightedness restores the equivalence between jungle equilibria and lexicographic welfare maximization. However, we also derive farsighted equilibria in which stronger agents withhold goods from weaker agents. Then, gift giving by stronger agents is needed to restore Pareto efficiency. Our results add to understanding coercion and the crucial assumptions underlying jungle economies.
Keywords: D51; D61; P52; 330; jungle economy; withholding; coercion; power